Pemanfaatan Gagang Hijau (Ulva Latuca L.) untuk Kehidupan Manusia - Putri, Ryana Tammi (Jurnal Agricultural Biosystem Engineering, 2025)
Indonesia is an archipelago with a long coastline. This condition has the potential to produce green stems (Ulva latuca). Ulva Latuca is a plant containing 25-26% ash. This illustrates that the mineral content of ulva latuca is quite high, so this plant has the potential to produce several minerals that are useful for health, have antioxidant, antibacterial, antifungal, anti-inflammatory properties and can be used as a face mask. The potential of ulva latuca allows this plant to receive special attention to be developed and also developed equipment in the process of utilizing several minerals contained in Ulva latuca. Keywords: Ulva Latuca, Mineral Content, Health, Potential Products, Utilization.